2005
DOI: 10.1080/10503300512331385188
|View full text |Cite
|
Sign up to set email alerts
|

Depth of emotional experience and outcome

Abstract: The relationship between theme-related depth of experiencing (EXP) and outcome was explored in experiential therapy with depressed clients. The study sought to investigate whether depth of EXP predicts outcome, whether change in depth of EXP over therapy predicts outcome, and how these factors compare with the therapeutic alliance as predictors of outcome. The sample consisted of 35 clients, each of whom received 16 to 20 weeks of therapy. Themes that had emerged across therapy were identified. Depth of EXP wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
2
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 104 publications
(78 citation statements)
references
References 19 publications
5
69
2
2
Order By: Relevance
“…Research on clients' experiencing continues to be an important focus of inquiry by HP researchers. Goldman, Greenberg, and Pos (2005) found that positive shifts in the quality of clients' exploration of their inner experience--as measured by the Client Experiencing Scale (Klein, Mathieu, Gendlin, & Kiesler, 1969)--was a stronger predictor of outcome than the working alliance in client-centered and emotion-focused psychotherapy for depression. Previous studies have also addressed the impact of therapist proposals on the depth of clients' self-exploration (Sachse, 1992;Sachse & Elliott, 2002) in therapy sessions and found that therapists' statements that were high in experiencing resulted in higher levels of clients' experiencing during therapy sessions and that the depth of therapist experiential focus predicted overall outcome (Adams & Greenberg, 1996).…”
Section: Qualitative Hprmentioning
confidence: 97%
“…Research on clients' experiencing continues to be an important focus of inquiry by HP researchers. Goldman, Greenberg, and Pos (2005) found that positive shifts in the quality of clients' exploration of their inner experience--as measured by the Client Experiencing Scale (Klein, Mathieu, Gendlin, & Kiesler, 1969)--was a stronger predictor of outcome than the working alliance in client-centered and emotion-focused psychotherapy for depression. Previous studies have also addressed the impact of therapist proposals on the depth of clients' self-exploration (Sachse, 1992;Sachse & Elliott, 2002) in therapy sessions and found that therapists' statements that were high in experiencing resulted in higher levels of clients' experiencing during therapy sessions and that the depth of therapist experiential focus predicted overall outcome (Adams & Greenberg, 1996).…”
Section: Qualitative Hprmentioning
confidence: 97%
“…Clients learn to approach, be aware of and tolerate contact with emotions, cognitively orient to and make meaning of emotional information, and finally transform emotion by accessing adaptive emotional resources (Pos & Greenberg, 2007). Through this process, new emotional reactions and meanings can emerge that can be integrated into cognitive-affective meaning structures and subsequently change them (Pos, Greenberg, & Goldman, 2005). Experiential therapists are taught that providing an empathically attuned relationship from the start of therapy will facilitate clients' EP by helping them feel safe enough to move their attention away from interpersonal concerns towards engaging fully in the therapy task of approaching their feelings (Pos, 2006;Watson, Goldman, & Vanaerschot, 1998).…”
Section: Empathy and Epmentioning
confidence: 99%
“…Their results demonstrated that the most important was whether resolution occurred once during psychotherapy: the clients who experienced a shift in their view of the other had significantly better treatment outcomes than the clients who did not. The study conducted by Goldman, Greenberg, and Pos (2005) on in-session emotional experiencing also speaks in favor of peak level of client's processing. The results underlined the role played by peaks of emotional experiencing reached by the client in the prediction of the treatment outcome.…”
Section: Discussionmentioning
confidence: 98%